Obesity related factors in school-aged children: A qualitative study - Santika Santika; Septian Andriyani; Asih Purwandari Wahyoe Puspita (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Childhood obesity among school-aged children has become an escalating public health concern in Indonesia. It significantly affects children’s physical, mental, and social well-being. Obesity arises from a complex interplay of biological, environmental, behavioral, and parenting-related factors. Purpose: To examine the contributing factors to obesity in school-aged children. Method: A qualitative research design was employed using a phenomenological approach. Data were collected through in-depth interviews with five parents of elementary school children (grades 1–6) who had been diagnosed with obesity. Each interview was conducted in one day, with a duration of no more than 30 minutes per Respondent. The data were analyzed through coding and theme identification. Results: The analysis revealed five primary themes contributing to childhood obesity: a sedentary lifestyle, genetic influences, eating habits and parenting style, frequent consumption of snacks and sugary drinks, and irregular sleep patterns and habits. Conclusion: Obesity in school-aged children is driven by an interaction of sedentary behavior, unhealthy lifestyle habits, parenting practices, high sugar intake, genetic predisposition, and poor sleep routines. Preventive measures should adopt a holistic approach involving families, schools, and the surrounding environment to instill healthy behaviors from an early age.